Shionone Attenuates Sepsis-Induced Acute Kidney Injury by Regulating Macrophage Polarization via the ECM1/STAT5 Pathway - Zhang, Biao; Xue, Yi; Zhao, Jin; Jiang, Huojun; Zhu, Jiaoli; Yin, Hao; Qiu, Yizhen; Hu, Aihao; Xu, Lingqi; Song, Yi; Wang, Xin (Frontiers in Medicine, 2022)
Aim: There is no approved target drug for acute kidney injury (AKI) due to sepsis. Shionone is a natural drug with anti-inflammatory activity. In this study, we sought to determine the functional role of Shionone in sepsis-induced AKI. Main methods: C57BL/6 mice were assigned to the Sham, CLP, DXM, 50 mg/kg Shionone and 100 mg/kg Shionone groups. Animal models of AKI were constructed by cecum ligation and puncture (CLP) surgery. Mouse macrophages RAW264.7 were divided into control, LPS, 1 μg/mL Shionone and 2 μg/mL Shionone groups. The cellular model of AKI was induced by LPS. HE staining assay was used to assess the pathological status, immunofluorescence staining and western blot were used to detect protein expressions, flow cytometry was used to detect macrophage typing, and the levels of pro-inflammatory factors IL-6, IL-12, IL-1β, TNF-α and anti-inflammatory factors IL-10 and TGF-β were measured using the corresponding kits. Key findings: Shionone may promoted M2 macrophages polarization via the GM-CSF/STAT5/Arg1 pathway to alleviate sepsis-induced AKI . Significance: These findings clarify that Shionone may be a promising target agent for sepsis-induced AKI.